Fun English Learning in Trauma Healing Programme - Wulandari Umar; Muh. Ilham Nur; Setiawan Wancie; Masruddin; Mursyid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Fun English learning can be part of a trauma healing programme to support the emotional recovery of participants, especially children. This method combines interactive activities such as games, music and role-play designed to create a positive and comfortable learning atmosphere. The purpose of this study is to determine the effect of fun English learning on participants' learning motivation and psychological recovery. This research uses a qualitative approach with observation and interviews as data collection techniques. The results show that this method not only improves participants' motivation and communication skills but also helps them reduce stress and anxiety. Thus, fun English learning plays an important role in accelerating the trauma recovery process and improving participants' social adaptation.